Professores negros, experiências de discriminação, de racismo e pedagogias anti-racistas - Machado, Lúcia Helena de Assis (2010)
The presente work has a objective the a analysis by the memory and telling of personal and professional experiences of discriminations and racism lived by eight black teachers, for through them to understand the position accepted by the same teachers up against the racial question, or in the school circle or out of it. It also analizes how the discriminatitory experiences contribute in bigger or smaller grade for these teachers build anti-racism strategies or educations with the object to finish with the racial discrimination and prejudice. The position of the teachers varied between a combative position of fight, silence, refuse, face in the personal circle till the build of strategies, even if in the individual fighter field of discrimination.